The Slow Depolarization Following Individual Spikes in Thin, Unmyelinated Axons in Mammalian Cortex - Raastad, Morten (Frontiers in Cellular Neuroscience, 2019)
An important goal in neuroscience is to understand how neuronal excitability is controlled. Therefore, Gardner-Medwin’s 1972 discovery, that cerebellar parallel fibers were more excitable up to 100 ms after individual action potentials, could have had great impact. If this long-lasting effect were due to intrinsic membrane mechanisms causing a depolarizing after-potential (DAP) this was an important finding. However, that hypothesis met resistance because the use of K+ sensitive electrodes showed that synchronous activation, as commonly used in excitability tests, increased extracellular K+ concentration sufficiently to explain much of the hyperexcitability. It is still controversial because intra-axonal recordings, which could have settled the debate, have not been made from parallel fibers or other axons of similar calibers. If it had not been for the fact that such thin axons are, by far, the most common axon type in cortical areas and control almost all glutamate release, it would be tempting to ignore them until an appropriate intra-axonal recording technique is invented. I will go through the literature that, taken together, supports the hypothesis that a DAP is an intrinsic membrane mechanism due to a well-controlled process that stops the fast repolarization at a membrane potential positive to resting membrane potential, leaving the membrane more excitable for ~100 ms during a slow, passive discharge of the membrane capacitance. The DAP helps reduce failures but can also cause uncontrolled bursting if it is not properly controlled. The voltage at which the fast repolarization stops, and the DAP starts, is close the activation range of both Na+ and Ca2+ voltage activated channels and is therefore essential for neuronal function.